2012
DOI: 10.1155/2012/547382
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Comprehensive Epilepsy Center in Pakistan: Initial Experiences, Results, and Reflections

Abstract: Background. Developing countries, home to 80% of epilepsy patients, do not have comprehensive epilepsy surgery programs. Considering these needs we set up first epilepsy surgery center in Pakistan. Methods. Seventeen teleconferences focused on setting up an epilepsy center at the Aga Khan University (AKU), Karachi, Pakistan were arranged with experts from the University of Alberta Hospital, Alberta, Canada and the University of West Virginia, USA over a two-year period. Subsequently, the experts visited the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…There were more studies that were included in our meta-analysis compared with prior meta-analyses by Josephson et al 5 and Hu et al 4. In particular, there were seven studies that were not included in prior meta-analyses—Arruda et al ,39 Renowden et al ,48 Tahir et al ,51 Sagher et al ,49 Bujarski et al ,41 Wendling et al 54 and Nascimento et al 46—which demonstrated no significant difference in seizure-free outcome of ATL versus SAH. The inclusion of new data from these studies may have contributed to differences in this study’s conclusion relative to prior meta-analyses.…”
Section: Discussionmentioning
confidence: 98%
“…There were more studies that were included in our meta-analysis compared with prior meta-analyses by Josephson et al 5 and Hu et al 4. In particular, there were seven studies that were not included in prior meta-analyses—Arruda et al ,39 Renowden et al ,48 Tahir et al ,51 Sagher et al ,49 Bujarski et al ,41 Wendling et al 54 and Nascimento et al 46—which demonstrated no significant difference in seizure-free outcome of ATL versus SAH. The inclusion of new data from these studies may have contributed to differences in this study’s conclusion relative to prior meta-analyses.…”
Section: Discussionmentioning
confidence: 98%
“…1). Six studies were excluded for the following reasons: non-blind randomized trial [18], number of patients less than 20 [19,20], followup for less than 1 year [21,22], and overlapping patient population [23]. Twenty-six articles which included 2930 cases (1390 cases under SAH and 1540 cases under ATL) met the inclusion criteria for metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Information on whether they had sufficient qualified personnel or adequate training was mainly not mentioned or difficult to extract. Some papers reported on collaborative work between HIC and LMIC in Uganda [36][37][38], Tunisia [41], Thailand, India and Argentina [83,105], Pakistan [168], and Iran [171]. The collaborative epilepsy surgery program between North America and the CURE Children's Hospital of Uganda (CCHU) assessed the feasibility of an epilepsy surgery program in a resource-poor setting using just videoelectroencephalography (EEG) and computed tomography (CT) volumetric analysis [38].…”
Section: Resultsmentioning
confidence: 99%
“…Table 5 showed that the indicators of QOL improved after surgery [37,47,50,59,93,98,101,122,126,134,159,160,165,175,177], except in one study [62]. Table 6 reports on the cost of epilepsy surgery [66,70,71,114,117,144,147,164,168,171,172] and VNS [138], the cost of epilepsy surgery as at 2014 ranges between US$500 in Iran to approximately US$8,000 in China.…”
Section: Tunisian Epilepsy Surgery Program At the Charles Nicolle Hosmentioning
confidence: 99%